2020
DOI: 10.1007/s40801-020-00199-3
|View full text |Cite
|
Sign up to set email alerts
|

The Real-World Economic and Clinical Management of Adult Patients with Skin and Soft Tissue Infections (SSTIs) with Oritavancin: Data from Two Multicenter Observational Cohort Studies

Abstract: Background Oritavancin is a FDA-approved single-dose IV therapy for the treatment of acute bacterial skin and skin structure infections caused (or suspected to be caused) by certain Gram-positive pathogens, including methicillin-resistant Staphylococcus aureus (MRSA). Published data describing the outcomes of patients with skin and soft tissue infections (SSTIs) who received oritavancin beyond its pivotal phase III clinical trials are scant. Objective The purpose of this report was to describe the results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In an assessment of 67 patients who received oritavancin at a community hospital, no readmissions and 8 ED return visits were observed within 14 days of discharge [18]. Similarly, the 30-day subsequent readmission rate was reported to be 6.1% in an evaluation of oritavancin for ABSSSI patients across three hospital-based outpatient infusion centers [19]. In our study, the observed 30-day readmission rate was slightly higher (9.8%), but this may have been due to the aggressive mandated pharmacy callback system, which encouraged patients to return to the hospital if symptoms were not completely resolved.…”
Section: Discussionmentioning
confidence: 99%
“…In an assessment of 67 patients who received oritavancin at a community hospital, no readmissions and 8 ED return visits were observed within 14 days of discharge [18]. Similarly, the 30-day subsequent readmission rate was reported to be 6.1% in an evaluation of oritavancin for ABSSSI patients across three hospital-based outpatient infusion centers [19]. In our study, the observed 30-day readmission rate was slightly higher (9.8%), but this may have been due to the aggressive mandated pharmacy callback system, which encouraged patients to return to the hospital if symptoms were not completely resolved.…”
Section: Discussionmentioning
confidence: 99%
“…The low 30-day readmission and infection progression rates observed among patients who received oritavancin are consistent with other studies of an identical nature. In a multicenter, retrospective study that evaluated the use of oritavancin upon hospital discharge to complete treatment of an SSTI, infection-related 30-day readmission rates were 2.6% [16]. Similarly, no patients had to be readmitted within 14 days of oritavancin therapy in an evaluation of oritavancin use at a community hospital to facilitate hospital discharge [17].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are the first line approach to treat SSTI, however their efficacy is rapidly decreasing in consequence of the growth of antibiotic resistance among pathogens. New antibiotics, such as oritavancin or delafloxacin, to treat SSTI, have emerged 7 , 8 ; nonetheless it is expected that antibiotic resistance will outpace the development of new drug thus different antimicrobial treatment is urgently needed.…”
Section: Introductionmentioning
confidence: 99%